A SYSTEMATIC ANALYSIS OF LITERATURE REVIEW STRATEGIES FOR IMPLEMENTING OUT-OF-SCHOOL EDUCATION IN REMOTE AREAS - Lisnawaty, Sri Dewi (PT Altin Riset Publishing, 2024)
This study aims to analyze the implementation strategies of out-of-school education (OSE) in remote areas through a systematic literature review (SLR) approach. The primary focus of this research is to identify the main challenges faced in implementing OSE in remote regions, analyze the role of various stakeholders in supporting OSE implementation, and formulate effective strategies that can enhance the quality and access to education in these areas. Additionally, this study aims to provide policy recommendations that can support the sustainability of OSE in remote regions. The research method used is a systematic literature review (SLR), which involves searching for and critically analyzing related literature that has been published. Data were collected from various sources, including reputable international journals and Sinta-accredited journals, which were then analyzed to identify patterns, themes, and gaps in previous research. The findings of the study indicate that the main challenges in implementing OSE in remote areas include limited transportation access, inadequate infrastructure, and a lack of technological support. Furthermore, the study found that the roles of stakeholders such as the government, NGOs, and local communities are crucial in supporting the success of OSE programs. Effective strategies to improve the quality and access to OSE include enhanced teacher training, the utilization of digital technology, and the adaptation of policies that align with local conditions. The proposed policy recommendations emphasize the need for sustained support from central and regional governments, as well as active community involvement in the education process.